The Wave Origins of Longitudinal Structures in ExoMars Trace Gas Orbiter (TGO) Aerobraking Densities. Issue 2 (10th February 2021) - Forbes, Jeffrey M.; Bruinsma, Sean; Zhang, Xiaoli; Forget, Francois; Marty, Jean‐Charles; Millour, Ehouarn; González‐Galindo, Francisco
Abstract: The nature and origins of longitudinal density structures in Mars' thermosphere between 100 and 120 km altitude, and −30° and −75° latitude around winter solstice (Ls = 70–122°), as measured by the accelerometer on the ExoMars Trace Gas Orbiter (TGO) Mission, are investigated. The methodology consists of deducing the responsible waves by comparing the observed longitude versus local time phase progressions of the structures with those of probable candidate waves in the Mars Climate Database (MCD) climatology. The observed wave‐1, wave‐2, and wave‐3 structures are interpreted as originating mainly from SPW1; (SPW2, S0, DE1); and (SPW3, DE2), respectively, where SPWm denotes a stationary planetary wave with zonal wavenumber s  =  m, S0 is the zonally symmetric semidiurnal tide, and DE1(DE2) are the eastward‐propagating diurnal tides with s  = −1(−2). All of these waves exist in the MCD with amplitudes as large as those observed, although not wholly in the narrow height‐latitude regime accessed by TGO. This disparity between the MCD and TGO amplitude structures is hypothesized to result from the extreme intrusion of the polar‐region eastward winter jet into the thermosphere in the MCD. The winter polar jet blocks poleward expansion of DE1 and DE2 beyond −30° latitude, and also impacts the structures of SPW2, S0 and SPW3 that arise from in situ nonlinear interaction between DE1 and DE2, respectively, with the diurnal migrating tide (DW1). Key Points: Longitudinal density structures measured by Mars TGO accelerometer are interpreted with insights provided by Mars Climate Database (MCD) Stationary planetary waves, some excited by in situ wave‐wave interactions, play a prominent role in explaining the density structures The MCD‐TGO comparison suggests that the intensity and vertical‐latitudinal extent of the winter polar jet may be overestimated in the MCD